Lembar Praktikalitas: Instrumen yang Digunakan untuk Menilai Produk yang Dikembangkan pada Penelitian Pengembangan Bidang Pendidikan - Cahaya, Nilam; Fauziah, Nurul; Ferazona, Sepita; Hidayati , Nurkhairo; Mellisa; Yeyendra (Biology and Education Journal, 2024)
The practicality sheet plays an important role in the usability process of a product to be developed. Practicality sheets have a big influence on the level of use of a product, namely being practical, easy to understand and enjoyable for teachers or students to use the product. This research aims to develop a practicality sheet that can be used as an instrument in assessing the product being developed. The product that has been developed must be validated by experts in the field of education. After the product is said to be valid then the product is field tested on students where the product is said to be practical if the experts say that theoretically this product can be applied in the field and the level of workability is good, therefore the aim of this research is to develop a practicality sheet in accordance with instruments that are valid and validated by expert validators in the field of education. The practicality sheet development procedure is based on the PLOMP model research and development. This research takes place at the development stage. This practicality sheet consists of a grid and assessment rubric. The grid contains aspects and indicators. The assessment rubric contains indicators and criteria for assessment scores by the validator, apart from that it also contains provisions for scoring the questionnaire. The practicality sheet consists of 4 aspects which cover various indicators, namely 1) The display aspect has 4 indicators (readability of text, clarity of presentation, use of font), 2) The linguistic aspect has 1 indicator (use of language), 3) The material aspect contains 3 indicators, namely (sequence, presentation of material and study materials), 4) Presentation aspect consisting of 1 indicator (motivation). The practicality sheet developed has been validated by educational validators and the overall practicality sheet assessment received a percentage of 96.6% with a very valid validity category. This shows that the practicality sheet developed can be used as an instrument to assess a product developed in educational development research.